Pengembangan Lembar Kerja Siswa (LKS) Berbasis Inkuiri Terbimbing Pada Pokok Bahasan Kesetimbangan Kimia - Lisnawaty Simatupang; Indah Santika (Universitas Negeri Medan, 2021)
Student worksheets are sheets that are used as guidelines in learning and contain tasks that must be done by students in certain studies. This study aims to see: (1) The design of student worksheets based on guided inquiry on the subject of chemical equilibrium; (2) analyzing the feasibility of student worksheets (LKS) based on guided inquiry learning models on chemical equilibrium material; (3) analyzing the response of student and teacher attractiveness to student-based student worksheets based on guided inquiry on the subject of chemical equilibrium. The research subjects were student worksheets based on guided inquiry. The object of research is the material of chemical equilibrium. The development of student worksheets refers to the research and development model of the Borg and Gall. This worksheet has been validated by validators / experts and has been through small group trials to obtain valid and interesting results. The results of this study indicate that: the results of validation by material experts get a percentage of 85% and the results of validation by media experts get a percentage of 88,57% with a very feasible category. Meanwhile, the results of the attractiveness based on the responses of the teacher and students got a percentage of 90% and 88.85% respectively, with the very interesting category.